AN ANALYSIS OF TEACHERS' INSIGHT TOWARDS STUDENT LEARNING STYLE - Riasty Latanya Sianturi; Kammer Tuahman Sipayung (Sean Institute, 2023)
Learning style is a way that individuals explain how individuals learn or how they are conducted each person to concentrate on the process. The learning styles are individual and should be able to provide information on the different ways each is learned individuals. The aim of this study is to find out the imagery of the learning styles. This study was done with qualitative research design with observation, survey and interview techniques to collect the data. The observation and survey was done to the students while teaching and learning process, however interview was done to confirm the information to the students and teacher. The population of this research is 190 students. Sample of this research is seventy students. This sample was chosen with purposive sampling, based on certain criteria. This research was done when doing kampus mengajar batch four. After collecting and analyzing the data, this research shown that twenty students are auditory, twenty students are visual and thirty students are reading. This findings will give a better impact on teaching method that the teacher should design in the proces of teaching and learning.